2012
DOI: 10.1007/s11255-012-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Goserelin versus leuprolide in the chemical castration of patients with prostate cancer

Abstract: There were no statistically significant differences in the levels of castration when comparing leuprolide 3.75 mg, leuprolide 7.5 mg, and goserelin 3.6 mg, altogether. When compared in groups of two, there was a statistically significant difference between leuprolide 3.75 mg and leuprolide 7.5 mg, the latter presented better results in reaching castration levels, cutoff ≤ 20 ng/dl. The importance of this difference, however, must be measured with caution, since the comparison of the three groups simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…4,8,16-18 These numbers rise even further to 13%-68% of patients for the stricter definition of castrate levels of testosterone <20 ng/dL. 4,8,16-19 Interestingly, even with bilateral orchiectomy, up to 25% of patients do not achieve <20 ng/dL of testosterone.…”
Section: Commentmentioning
confidence: 98%
“…4,8,16-18 These numbers rise even further to 13%-68% of patients for the stricter definition of castrate levels of testosterone <20 ng/dL. 4,8,16-19 Interestingly, even with bilateral orchiectomy, up to 25% of patients do not achieve <20 ng/dL of testosterone.…”
Section: Commentmentioning
confidence: 98%
“…Multivariate analyses from Morote et al support a lower T threshold for both the initial target level and those seen throughout maintenance of [53] Safety Adverse effects in ‡ 15% of patients in any study [5,20,[45][46][47]54] Hot flashes, fatigue 2008 *LH-RH antagonist; z Kaplan--Meier (K-M) estimate within group from week 4 --48 for minimum only; § K-M estimates from day 57-end of study; { K-M estimates within group from day 28 --364; # Data available for 1-month formulation only [32]; **Data available for 3-month formulation only [55]; zz Data available for 1-month formulation only [48]; § § Extrapolated from K-M estimates days 57-end of study; {{ Data available for 3-month formulation only. LH-RH: Luteinizing hormone-releasing hormone.…”
Section: Optimal Serum T Level In Adtmentioning
confidence: 99%
“…Adding to this complex and challenging scenario is the fact recently confirmed by our group that the efficiency of the different available pharmacological castration solutions aimed at reaching castration levels, mainly for cutoff %20 ng/dl, can vary significantly; surprisingly, about half and one-third of patients did not achieve castration levels of 20 and 50 ng/dl respectively (Silva et al 2012).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…It is of concern that although in the last 2 years, three approved treatments based on Phase III trials have demonstrated modest survival improvements (measured in months) in CRPC (cabazitaxel (potent taxane able to bypass the main resistance mechanism to docetaxel drug efflux pump, P-glycoprotein 1; approved in 2010); sipuleucel-T (immunotherapeutic agent through dendritic cells; approved in 2010); and abiraterone (orally active, potent and irreversible inhibitor of CYP17 -a critical enzyme in androgen biosynthesis; approved in 2011)), palpable advancement in hormonal management has been scarce and underexplored (Reis 2011, Silva et al 2012.…”
Section: Endocrine-related Cancermentioning
confidence: 99%